Monitoring the Environmental Temperature of the Arduino Assistance Engineering Faculty Using Telegram - Hariyanto, M Wujut; Hendri Hendrawan, Ade; Ritzkal, Ritzkal (Journal of Robotics and Control (JRC), 2020)
The temperature of the air is the state of hot air caused by the heat of the sun. Factors that affect the amount of solar heat received by the earth are cloud, the surface plane, the angle of the sun, and the length of the sun's exposure. The heat of the earth's surface by solar radiation affects the heat of the air. Earth's surface air temperature varies because sunlight spreads unevenly on the earth's surface. The research aimed to design and implement a series of tools that can measure the ambient temperature and provide information about the environmental temperature via telegram. The methods used in this research were analyses consisting of needs analysis, and analysis of how it worked. Hardware and software implementations were also applied. The research carried out several tests, including tests on the DHT11 sensor, LED light, LCD i2c, Ethernet Shield, and Telegram test. The integration test on the LCD showed that when the temperature was below or the same as 25ËšC, the green LED would be ON and the red LED OFF, which indicated that it was cold temperature. Conversely, when the temperature was the same or above 30ËšC, the red LED would be ON, and the green LED OFF, indicating that the temperature was hot. The second test was to compare digital and analog sensors. The comparison values of the digital and analog temperatures were 1.1ËšC, and the humidity was 23.1% RH. The highest temperature obtained from the system per day was 34ËšC, and the lowest temperature was 23ËšC.